A long chain-induced depletion effect for abnormal grafting in the preparation of bimodal bidisperse polymer-grafted nanoparticles. Issue 7 (2nd February 2023) - Li, Chu-Xiang; Mao, Jin-Yuan; Li, Shu-Jia; Wang, Yan; Liu, Hong
Abstract : The results obtained by our simulations can provide effective guidance for the design of nanoparticle-grafted bimodal bidisperse polymer chains and provide a theoretical basis for experimentation and production of polymer nanocomposites with better performance. Abstract : One of the challenging problems in the research field of polymer nanocomposites is how to prepare nanocomposites with high grafting density and strong ability of dispersion at the same time. For nanocomposites composed of bimodal bidisperse polymer chains and nanoparticles, the above requirements can be met by rationally adjusting the ratio of long and short polymer chains. In this study, the process of grafting bimodal bidisperse polymer chains onto the surface of nanoparticles in a grafting-to manner was investigated via computer simulation and theoretical methods. Three grafting strategies were designed: first short then long (SL) system, both short and long (Both) system and first long then short (LS) system. An abnormal phenomenon for the Both system was found by analyzing the grafting density of long and short polymer chains on the surface of nanoparticles. We speculate that the reason for this anomalous phenomenon is the "depletion effect" brought about by the long chains in the Both system. We employ the Polymer Reference Interaction Site Model (PRISM) theory to investigate this anomaly in-depth. By comparing the radial distribution function (RDF) predicted by the PRISM theory with the RDF results obtained by the molecular dynamics (MD) simulation, we found that with the increase of the number of long chains in the system, the grafting density of short polymer chains on the nanoparticle surface showed an obvious upward trend. The "depletion effect" brought by long chains was the main reason for higher short chains' grafting density of the Both system compared to the SL system. Our findings provide effective guidance for the design of nanoparticle-grafted bimodal bidisperse polymer chains and provide a theoretical basis for experimentation and production of polymer nanocomposites with better performance.